Cochlear implantation and auditory brainstem implantation in neurofibromatosis type 2. (24th March 2018) - Peng, Kevin A.; Lorenz, Mark B.; Otto, Steven R.; Brackmann, Derald E.; Wilkinson, Eric P.
Abstract : Objectives/Hypothesis: To report a series of patients with neurofibromatosis type 2 (NF2), where each patient underwent both cochlear implantation and auditory brainstem implantation for hearing rehabilitation, and to discuss factors influencing respective implant success. Study Design: Retrospective case series. Methods: Ten NF2 patients with both cochlear implantations and auditory brainstem implantations were retrospectively reviewed. Speech testing for auditory brainstem implants (ABIs) and cochlear implants (CIs) was performed separately. Scores at last follow‐up were obtained for Iowa vowels and consonants, Northwestern University Children's Perception of Speech (NU‐CHIPS), and City University of New York (CUNY) sentences. Results: Mean age at time of implant was 37 years for cochlear implantation and 40 years for auditory brainstem implantation ( P = .790, t test). Nine of 10 patients had a CI and ABI on contralateral sides, and one had both devices on the same side. Mean duration of deafness in the implanted ear was 4.3 years for both cochlear implantation and auditory brainstem implantation ( P = .491, t test). Follow‐up range was 1 to 28 years. CI performance on NU‐CHIPS was 32% to 100%, and sound + lip‐reading CUNY was 56% to 100%. Four patients experienced an eventual decline in CI function to unusable levels. ABI performance on NU‐CHIPS was 40% to 80%, and sound + lip‐reading CUNY was 38% to 94%. There was no notable decline in ABI function over time. Conclusions: If the cochlear nerve is intact, cochlear implantation can be an effective strategy for hearing rehabilitation in NF2. However, a significant proportion experience a decline in CI performance related to growing vestibular schwannoma or tumor treatment. Auditory brainstem implantation remains the standard option for surgical hearing rehabilitation in NF2, but peak performance is generally lower than that achievable with cochlear implantation. Level of Evidence: 4. Laryngoscope, 128:2163–2169, 2018